Combined associations of a polygenic risk score and classical risk factors with breast cancer risk - Kapoor, Pooja Middha; Behrens, Sabine; Arndt, Volker; Brenner, Hermann; Canzian, Federico; Hamann, Ute; Kaaks, Rudolf; Schöttker, Ben; Chang-Claude, Jenny (Journal of the National Cancer Institute, 2021)
We evaluated the joint associations between a new 313-variant PRS (PRS313) and questionnaire-based breast cancer risk factors for women of European ancestry, using 72 284 cases and 80 354 controls from the Breast Cancer Association Consortium. Interactions were evaluated using standard logistic regression and a newly developed case-only method for breast cancer risk overall and by estrogen receptor status. After accounting for multiple testing, we did not find evidence that per-standard deviation PRS313 odds ratio differed across strata defined by individual risk factors. Goodness-of-fit tests did not reject the assumption of a multiplicative model between PRS313 and each risk factor. Variation in projected absolute lifetime risk of breast cancer associated with classical risk factors was greater for women with higher genetic risk (PRS313 and family history) and, on average, 17.5% higher in the highest vs lowest deciles of genetic risk. These findings have implications for risk prevention for women at increased risk of breast cancer.
First published: 02 May 2020
Gesehen am 18.06.2021